2023
DOI: 10.1111/bjet.13305
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of needs satisfaction on the relationships between prior knowledge and self‐regulated learning through artificial intelligence chatbot

Abstract: The anthropomorphic characteristics of artificial intelligence (AI) can provide a positive environment for self-regulated learning (SRL). The factors affecting adolescents' SRL through AI technologies remain unclear. Limited AI and disciplinary knowledge may affect the students' motivations, as explained by self-determination theory (SDT). In this study, we examine the mediating effects of needs satisfaction in SDT on the relationship between students' previous technical (AI) and disciplinary (English) knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 84 publications
(137 reference statements)
5
24
0
2
Order By: Relevance
“…SRLbot In RQ3, quantile regression analysis indicates that the number of by students has higher slope estimates compared to gender when using SRLbot. Additionally, the effects of students' interactions on their SRL are significant across all quantiles when utilizing AI chatbots, which aligns with previous studies Xia et al, 2023). Maldonado-Mahauad et al (2022) have suggested a possible explanation for this, stating that increased interaction with generative AI chatbots makes it easier to ascertain their impact on SRL.…”
Section: Benefits Limitationssupporting
confidence: 88%
“…SRLbot In RQ3, quantile regression analysis indicates that the number of by students has higher slope estimates compared to gender when using SRLbot. Additionally, the effects of students' interactions on their SRL are significant across all quantiles when utilizing AI chatbots, which aligns with previous studies Xia et al, 2023). Maldonado-Mahauad et al (2022) have suggested a possible explanation for this, stating that increased interaction with generative AI chatbots makes it easier to ascertain their impact on SRL.…”
Section: Benefits Limitationssupporting
confidence: 88%
“…We included these two covariates due to their significant correlation with perception outcomes measures, and thus their inclusion will improve the precision of model estimates. Other prior studies also suggested the role age and prior knowledge played in people's perceptions of AI [55,56]. Results are displayed in Table 5.…”
Section: Effects Of Transparency and Framing On Perceptionmentioning
confidence: 73%
“…Third, educational need analysis may help specify the role of artificial intelligence chatbots in particular educational contexts, which demonstrates the perspective of characteristics and functions regarding technologies (Xia et al , 2023 for the effects of need satisfaction). As the clustering results and the existing literature reviews have revealed, chatbots’ functions are currently limited.…”
Section: Discussionmentioning
confidence: 99%